STRATEGI DAKWAH HIMPUNAN MAHASISWA KOMUNIKASI DAN PENYIARAN ISLAM DALAM MENINGKATKAN MINAT BACA MAHASISWA STIBA AR RAAYAH SUKABUMI - Hidayat, Tatang; Walangadi, Ridwan; Istianah, Istianah (Jurnal Al-Hikmah: Jurnal Dakwah, 2024)
The wealth of natural resources cannot guarantee the advancement of a human civilization. It is proven that human resources play an important role in determining the quality of a nation. Students as the future successors of the nation should have broad insights and horizons of knowledge to solve problems in society. The purpose of this research is to analyze HIMA KPI's da'wah strategy in increasing students' interest in reading, especially STIBA Ar Raayah Sukabumi students. This research uses qualitative research methods with a descriptive approach. Data were collected through participatory observation, interviews, and analysis of documents related to HIMA KPI's da'wah activities. The results of the study, To increase students' interest in reading, HIMA KPI STIBA Ar Raayah has made several efforts. The use of mading (wall magazine) in the campus environment can be an effective visual communication tool to convey information and encourage students to read more. In addition, scientific seminars can also provide benefits in increasing knowledge, experience, and expanding relationships. With efforts such as mading and scientific seminars, it is hoped that student interest in reading can increase. This will have a positive impact in supporting da'wah and the spread of Islamic values in society.